Profit generation or community resource?: Studying attitudes to the operation of a post office by a charity. Issue 3 (7th November 2016) - Bishop, Neil; Ridley-Duff, Rory; Morgan, Gareth
Abstract : Purpose: For the past decade, sub-post offices (POs) in the UK have been subject to intensive pressures to marketise their business. Actual or threatened closures have led charities to become involved in projects to preserve community post offices. This paper aims to investigate the attitudes of the trustees and staff involved in six charity-backed POs to answer the research question "Do those involved with charity-backed POs prioritise profit generation or community resourcing?" Design/methodology/approach: This research adopted a neo-empiricist stance on the collection and interpretation of data. The authors treated "attitudes" as real phenomena that are subjectively experienced and concretely expressed through activities in an objectively real world. Data were gathered from four or more people in each of six POs by sampling their services and conducting face-to-face interviews. The emphasis was on achieving verstehen – a rich understanding of a specific approach to social enterprise grounded in interpretations of human activity under conditions of naturalistic inquiry. Findings: The authors found that charity-backed POs were focussed on preserving POs as a community resource but articulated this by framing profitability in three distinct ways: as a PO generating a surplus that can be gifted or reallocated to a (parent) charity's other activities; as an activity that offsets a charity's fixed costs; or enables or promotes its public benefit aims. Research limitations/implications: There are few peer-reviewed studies of the potential of sub-POs as sites for social enterprise, and none (that could be located) on the role of charities. In this study, the authors contest Liu and Ko's view (2014, p. 402) that the key task is "to install market-oriented managerial beliefs and values into the charity retailer's decision-making". A counter view is offered that trading can represent a further diversification of the innovations used to support charitable endeavours. Originality/value: This is the first academic study to confront the complexities of differentiating "profitability" from "profit generation" in charity-backed POs. The subtleties in the articulation of this difference by study participants helped to account for the findings of the study and to make sense of the strong consensus that POs should be seen primarily as a community resource while responding to marketisation pressures.